2016
DOI: 10.1016/j.pbiomolbio.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Dominant negative consequences of a hERG 1b-specific mutation associated with intrauterine fetal death

Abstract: The human ether-a-go-go related gene (hERG) encodes two subunits, hERG 1a and hERG 1b, that combine in vivo to conduct the rapid delayed rectifier potassium current (IKr). Reduced IKr slows cardiac action potential (AP) repolarization and is an underlying cause of cardiac arrhythmias associated with long QT syndrome (LQTS). Although the physiological importance of hERG 1b has been elucidated, the effects of hERG 1b disease mutations on cardiac IKr and AP behavior have not been described. To explore the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…In contrast, fluoxetine appeared to be a more potent blocker of hERG1a/1b than hERG1a channels 33 . Furthermore, multiple studies have confirmed the importance of hERG1a/1b in maintaining normal physiological function in the human heart 31,32,34,51 . Hence, apart from hERG1a channel, it is important to investigate inhibition potential of drugs on hERG1a/1b channels given the different gating properties and drug sensitivities of the isoforms.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, fluoxetine appeared to be a more potent blocker of hERG1a/1b than hERG1a channels 33 . Furthermore, multiple studies have confirmed the importance of hERG1a/1b in maintaining normal physiological function in the human heart 31,32,34,51 . Hence, apart from hERG1a channel, it is important to investigate inhibition potential of drugs on hERG1a/1b channels given the different gating properties and drug sensitivities of the isoforms.…”
Section: Discussionmentioning
confidence: 93%
“…To determine whether native I Kr is affected by TRIOBP-1 overexpression, we performed patch-clamp electrophysiology experiments in cardiomyocytes derived from human induced pluripotent stem cells (iPSC-CMs) (Harley et al, 2016;Jones et al, 2014Jones et al, , 2016Ma et al, 2011). I Kr , measured as an E-4031sensitive current (see Materials and Methods), was markedly reduced by TRIOBP-1 overexpression (Fig.…”
Section: Triobp-1 Overexpression In Human Cardiomyocytes Reduces I Krmentioning
confidence: 99%
“…iPSC-CM recordings were conducted at 5-30 days post plating. All iPSC-CM recordings were completed 48-96 h post transfection at 36±1°C using whole-cell patch-clamp as described previously (Jones et al, 2016). We only recorded from cells that displayed GFP fluorescence, which corresponds to successful Kir2.1 transduction.…”
Section: Hipsc-cmsmentioning
confidence: 99%
“…Interactions between hERG1a and hERG1b isoforms may have relevance for drug block and acquired LQTS because there is a difference in affinity for drugs between currents from HEK293 cells expressing hERG1a compared with hERG1a plus hERG1b (32). Furthermore, hERG1a and hERG1b assembly may differently affect isoform-specific LQT mutations that selectively disrupt hERG1a (33,34) or hERG1b (15,35).…”
Section: Direct Herg1a and Herg1b Interactionsmentioning
confidence: 99%